2018
DOI: 10.1111/febs.14402
|View full text |Cite
|
Sign up to set email alerts
|

The C‐terminal cytosolic domain of the human zinc transporter ZnT8 and its diabetes risk variant

Abstract: A significant aspect of the control of cellular zinc in eukarya is its subcellular re‐distribution. One of the four human vesicular zinc transporters, ZnT8, supplies the millimolar zinc concentrations of insulin granules in pancreatic β‐cells, affecting insulin processing, crystallisation and secretion. ZnT8 has a transmembrane and a C‐terminal cytosolic domain; the latter has important functions and purportedly mediates protein–protein interactions, senses cytosolic zinc and/or channels zinc to the transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 49 publications
8
54
0
Order By: Relevance
“…This enables ZnT, in contrast to YiiP, to discriminate between Zn 2+ and the toxic ion Cd 2+ [81]. Other studies point to the cytoplasmic domain as important for transporter activity as described for ZnT8 [60], as well as in ZnT10 where a L349P missense mutation in the CTD affects transporter activity, and a synonymous mutation (M250P) in the prokaryotic CDF protein, MamM, was found to be critical for the CTD fold illustrating the importance of the CTD [82]. The identification of a CDF superfamily lacking the CTD, however, points to additional strategies for zinc transport by ZnT transporters [43].…”
Section: Znt Transportersmentioning
confidence: 95%
See 1 more Smart Citation
“…This enables ZnT, in contrast to YiiP, to discriminate between Zn 2+ and the toxic ion Cd 2+ [81]. Other studies point to the cytoplasmic domain as important for transporter activity as described for ZnT8 [60], as well as in ZnT10 where a L349P missense mutation in the CTD affects transporter activity, and a synonymous mutation (M250P) in the prokaryotic CDF protein, MamM, was found to be critical for the CTD fold illustrating the importance of the CTD [82]. The identification of a CDF superfamily lacking the CTD, however, points to additional strategies for zinc transport by ZnT transporters [43].…”
Section: Znt Transportersmentioning
confidence: 95%
“…It is expressed in pancreatic beta cells and functions as target autoantigen in patients with type 1 diabetes [59]. A common W325R variant in the ZnT8 large C-terminal domain (CTD) has been associated with changed autoantibody specificity in type 1 diabetes as well as increased risk of developing type 2 diabetes [60]. ZIP14 and ZIP4 were also found to be involved in diabetes as altered zinc trafficking in Zip14 −/− mice resulted in a phenotype with defects in glucose homeostasis [45], and in the murine pancreatic beta cell line MIN6, overexpression of ZIP4 leads to increased granular zinc content and glucose-stimulated insulin secretion [50].…”
Section: Diabetesmentioning
confidence: 99%
“…A recent (>44K) exome sequencing study reported >30 alleles in SLC30A8 reducing the risk of T2D, confirming it as a robust target for T2D protection 4 . Further, the SLC30A8 gene also harbors a common variant (rs13266634, c.973T>A) p.Trp325Arg in the C-terminal domain 5 . While the major p.Arg325 allele (>70% of the population) confers increased risk for T2D, the minor p.Trp325 allele is protective 6 .…”
Section: Introductionmentioning
confidence: 99%
“…We also reported a protective frameshift allele p.Lys34Serfs50* conferring 83% protection against T2D in Iceland 3 . Further, the SLC30A8 gene harbors a common variant (rs13266634, c.973C>T) p.Trp325Arg in the C-terminal domain 4 . Whilst the major p.Arg325 allele (>70% of the population) confers increased risk for T2D, the minor p.Trp325 allele is protective 5 .…”
mentioning
confidence: 99%